Teachers Helping EFL Students Improve Their Writing Through Written Feedback: The Case of Native and Non-native English-Speaking Teachers' Beliefs - Cheng, Xiaolong; Zhang, Lawrence Jun (Frontiers in Psychology, 2022)
While many prior studies have examined the effects of teacher written feedback on second language (L2) learners’ writing performance, relatively few studies have been conducted from feedback practitioners’ perspectives to investigate teachers’ beliefs regarding it, particularly compare beliefs held by teachers with different sociocultural and linguistic backgrounds. Consequently, little is known about how teachers of different first languages (L1) conceptualize written feedback. To fill this important gap, we conducted this qualitative study to compare native English-speaking (NES) and nonnative English-speaking (NNES) (Chinese L1) teachers’ beliefs in Chinese tertiary EFL settings. We analyzed the in-depth interviews with eight teachers through thematic analysis. The findings showed that both NES and NNES teachers espoused a range of beliefs in relation to the five themes of written feedback: Purpose, scope, focus, strategy, and orientation. The two groups of teachers shared similar beliefs with regard to feedback focus. However, their beliefs differed in terms of feedback scope. We conclude our study with a discussion on the important implications for educational practice.